Evaluating the Regional Expansion of Brazil’s Federal System of Vocational and Technological Education - Carazza, Luís; Silveira Neto, Raul da Mota (Revista Brasileira de Estudos Regionais e Urbanos, 2022)
This present study investigates whether some of the Brazilian government’s proposals have been accomplished, and especially the impact of creating federal institutes (FIs) on a set of migration and human capital variables. The expansion of the Brazilian Federal System of Professional and Technological Education between 2000 and 2010 created more than 150 new federal institutes offering high school, vocational and higher education. A new FI affected the proportion of new immigrants in the municipality of its location. More precisely, there was an increase of 1.98% in the proportion of new immigrants in the municipalities with new FIs. This means there were increases in the ratio of people who migrated and lived less than five years in the municipalities with a new FI, strengthening the role of FIs as an attractor of immigrants. Moreover, Brazil achieved the interiorization of education due to the expansion of federal institutes.